SGT1 is not required for plant LRR‐RLK‐mediated immunity. (11th November 2020) - Yu, Gang; Xian, Liu; Zhuang, Haiyan; Macho, Alberto P.
Abstract: Plant immune signalling activated by the perception of pathogen‐associated molecular patterns (PAMPs) or effector proteins is mediated by pattern‐recognition receptors (PRRs) and nucleotide‐binding and leucine‐rich repeat domain‐containing receptors (NLRs), which often share cellular components and downstream responses. Many PRRs are leucine‐rich repeat receptor‐like kinases (LRR‐RLKs), which mostly perceive proteinaceous PAMPs. The suppressor of the G2 allele of skp1 (SGT1) is a core immune regulator required for the activation of NLR‐mediated immunity. In this work, we examined the requirement of SGT1 for immune responses mediated by several LRR‐RLKs in both Nicotiana benthamiana and Arabidopsis . Using complementary genetic approaches, we found that SGT1 is not limiting for early PRR‐dependent responses or antibacterial immunity. We therefore conclude that SGT1 does not play a significant role in bacterial PAMP‐triggered immunity. Abstract : Using complementary genetic approaches in both Nicotiana benthamiana and Arabidopsis, this article shows that SGT1 does not play a significant role in bacterial PAMP‐triggered LRR‐RLK‐mediated immunity.